2009
DOI: 10.1016/s0924-9338(09)70491-2
|View full text |Cite
|
Sign up to set email alerts
|

Low Bone Mineral Density and Psychosis: A Multifactorial Relation

Abstract: Aims:Low bone mineral density (BMD) is a major public health issue leading to fractures, pain and disability. The association between psychosis and low bone density has been suggested in the last years.Method:The authors review the literature in Medline database using the words ‘bone mineral density’, ‘psychosis’, ‘antipsychotic’, ‘schizophrenia’, ‘bipolar disorder’ and ‘psychiatry disorders’.Results:Some studies show elevated prevalence of changes in BMD in patients with psychiatry disorders, namely psychosis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…The onset of schizophrenia occurs primarily in adolescents and young adults, where peak bone mass is yet to be achieved ( Forns et al, 2021 ; Zhu and Zheng, 2021 ). Patients with schizophrenia are possibly vulnerable to bone defects due to lifestyle factors such as a reduced physical activity, smoking, alcohol consumption, vitamin D deficiency and poor dietary habits in addition to genetic and biological factors ( Coentre et al, 2009 ). A study has shown that smoking and alcohol consumption also leads to further reduced BMD in patients with schizophrenia compared to those who do not smoke or drink alcohol ( Jung et al, 2011 ).…”
Section: Schizophrenia and Bone Health: Epidemiological Findingsmentioning
confidence: 99%
See 1 more Smart Citation
“…The onset of schizophrenia occurs primarily in adolescents and young adults, where peak bone mass is yet to be achieved ( Forns et al, 2021 ; Zhu and Zheng, 2021 ). Patients with schizophrenia are possibly vulnerable to bone defects due to lifestyle factors such as a reduced physical activity, smoking, alcohol consumption, vitamin D deficiency and poor dietary habits in addition to genetic and biological factors ( Coentre et al, 2009 ). A study has shown that smoking and alcohol consumption also leads to further reduced BMD in patients with schizophrenia compared to those who do not smoke or drink alcohol ( Jung et al, 2011 ).…”
Section: Schizophrenia and Bone Health: Epidemiological Findingsmentioning
confidence: 99%
“…Data taken from (34,64,(140)(141)(142). Binding affinity for receptors: + = week association (Ki value 100-1,000); ++ = Moderate association (10-91); +++ = strong association (Howes et al, 2009;De Hert et al, 2011;Patel et al, 2014;Fraser et al, 2015;Lally and MacCabe, 2015;Hálfdánarson et al, 2017;Haddad and Correll, 2018;Wang et al, 2021a;Australian Institute of Health and Welfare, 2022;Azimi Manavi et al, 2023); ++++ = very strong association (Ki < Frontiers in Cell and Developmental Biology frontiersin.org deficiency and poor dietary habits in addition to genetic and biological factors (Coentre et al, 2009). A study has shown that smoking and alcohol consumption also leads to further reduced BMD in patients with schizophrenia compared to those who do not smoke or drink alcohol (Jung et al, 2011).…”
Section: Schizophrenia and Bone Health: Epidemiological Findingsmentioning
confidence: 99%